(untitled) (Multidisciplinary Journal of Science and Technology, 2025)
The main purpose of this article is clinical death during cardiopulmonary resuscitation in terminal conditions in children - a condition with a transitional period between life and biological death, characterized by a complete absence of consciousness, respiration and blood circulation, heart contraction and ventricular enlargement. Respiratory arrest in children can be caused by severe injuries, drowning, chemical poisoning, toxicosis, inflammatory diseases, and airway obstruction.Intensive care is a comparative assessment of care and identification of the main causes of diseases in children.